Agreeing EPA rules of origin : a strategy unfolds - Pearson, Mark (2007)
Suggests that it is essential for the African, Caribbean and Pacific (ACP) Group of countries, negotiating the EPAs with the European Union to agree to rules of origin that are both liberal and clear. Opines that in the context of the EPAs, if these rules are difficult to fulfil, they will cause significant delays or will involve high costs for exporters, and many of the potential advantages of the trade agreements will be cancelled out.